Applying theory of constraints on the Indian administrative services - Mishra, Soumya; Palo, Sasmita (2014)
This paper attempts to identify constraints faced by Indian Administrative officers using the Theory of Constraints (ToC). Results show that despite its origins as a manufacturing methodology, Goldratt's ToC can be applied to identify constraints in the Indian administrative system, the most likely cause-and-effect relationships leading to such constraints, and the courses of action that are generally taken by officers to eliminate them. Three categories of constraints clearly emerged as inhibitors to the efficiency of the system. These are structural, policy and resources related. Lack of adequate training and insensitivity of officers towards the ground realities of the public are identified as some of the other constraints. It is observed that most of the respondents offered institutional arguments to characterize constraints in the system. Institutional arguments are not about assemblage of individual actions, but higher order factors above the individual level that influence the processes and outcomes and tend to sire regular patterns or inertia. - Reproduced.
Keywords: IAS; Civil service - India; Civil service